1963
DOI: 10.1071/ar9630646
|View full text |Cite
|
Sign up to set email alerts
|

The importance of liquid-seed contact during the germination of Medicago tribuloides Desr.

Abstract: At a given matric potential, rates of uptake of water and rates of seed germination on a suction plate apparatus were increased by improving the degree of contact between liquid water and seed. The conclusion of Collis-George and Sands (1962) that small matric potentials, as such, influence the rate of seed germination is critically reviewed in the light of the present investigation. The rate of germination of seeds was not influenced by small pressure potentials, which like matric potentials are a non-osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…In the first study there was a decrease in germination of almost 40% in the oversown treatment compared with the cultivated treatment for the four accessions with a level of germination exceeding 15%. This was probably attributable to poor contact between seed and water in the oversown treatment, as shown by Sedgley (1963) and McWilliam & Dowling (1970).…”
Section: Discussionmentioning
confidence: 86%
“…In the first study there was a decrease in germination of almost 40% in the oversown treatment compared with the cultivated treatment for the four accessions with a level of germination exceeding 15%. This was probably attributable to poor contact between seed and water in the oversown treatment, as shown by Sedgley (1963) and McWilliam & Dowling (1970).…”
Section: Discussionmentioning
confidence: 86%
“…Collis-George & Hector, 1966; Seed imbibition rates and the rate and level of Hadas & Stibbe, 1973; Hadas germination generally decrease as i/f^^^i decreases & Russo, 1974 a, b). Slight changes in ^^ are (Doneen & MacGillivray, 1943;Hunter & Erickson, accompanied by simultaneous changes in soil water 1952;Collis-George & Sands, 1959, 1962 Collis-conductivity and seed-soil contact area, whilst George & Hector, 1966;Williams & Shaykewich, changes in i/f^ per se are not (Sedgley, 1963;Collis-1971). A seed must absorb a certain amount of water George & Hector, 1966;Hadas, 1970;Hadas & to germinate, the critical hydration level being Russo, 1974a, 6).…”
Section: Introductionmentioning
confidence: 99%
“…This water transport, especially at lower water contents of the soil, is dependent on the matric potential. The water uptake by the seed, being a diffusion process, is also determined by the nature and the size of the contact area between seed and soil water (Sedgley 1963; Collis-George & Hector 1966). Experiments of Collis-George & Sands (1959,1962) and McWilliam, Clements & Dowling (1970) on sintered glass plates and in solutions of polyethylene-glycol or mannitol showed that a lower water potential of the medium was associated with a specific decrease in germination rate and percentage.…”
Section: Introductionmentioning
confidence: 99%